An exploratory study of community college Assessment-of-Learning Programs in the higher learning commission region - Rothgeb, Ray D. (Kansas State University, 2008)
This study used a mixed method designed to explore differences in institutional dynamics (Type and Accreditation Method), administrative qualities and characteristics (CAO/CEO Tenure and Management Style), and program support (Money Spent on Assessment and Mission Language) for community college assessment-of-learning programs in the Higher Learning Commission region. Chief Academic Officers from 83 "Community Colleges" in 17 states responded to an on-line quantitative survey (Assessment-of-Student-Learning Program Success [ASLPS]). T test analysis indicated significant differences in ASLPS scores when comparing AQIP with PEAQ institutions and when comparing institutions that included assessment-of-learning language in their mission statements with those that did not. Ten Chief Academic Officers, representing institutions with highest and lowest composite ASLPS scores, were interviewed for the qualitative study. Five "Traits of Perceived Successful Assessment-of-Learning Programs" were derived from the qualitative research.
Keywords: Assessment-of-learning; Community College; Education, Community College (0275)